Management of Human Resources Development of Taman Pendidikan Al Qur'an (TPQ) Assyamsuddluha in a Village: Manajemen Pengembangan Sumber Daya Manusia Taman Pendidikan Al-Qur’an (TPQ) Assyamsuddluha di Sebuah Desa - Khoirul Anwar Bani Sutar; Taufiq Churrahman (Academia Open, 2022)
This study aims to: (1) describe the management of human resource development of TPQ Assyamsud Dluha in Trawas sub-district, Mojokerto district, (2) describe the factors that influence the management of human resource development of TPQ Assyamsud Dluha in Trawas sub-district, district Mojokerto . This research is a type of qualitative research, by taking the research location in Taman Pendidikan Al Qur'an (TPQ) Assyamsud Dluha, Belik village, Trawas district, Mojokerto district. Data collection techniques used are observation, interviews, and documentation. Analysis of the data used is an interactive model from Miles and Huberman. The results of the study show that: First, TPQ Assyamsud Dluha has attempted to develop human resources started by the planning process, implementation, and evaluation. The development is carried out through education and training (training) using the Nahdliyah method. Second, the factors that influence the development of TPQ Assyamsud Dluha's human resources include: low skills (ability) of human resources, low mentality of human resources and diverse socio-cultural conditions of the community so that it is not easy to combine them together to achieve institutional goals.